Depth-dependent density change within the continental upper mantle - TENZER, Robert; BAGHERBANDI, Mohammad; VAJDA, Peter (Contributions to Geophysics and Geodesy, 2012)
The empirical model of the depth-dependent density change within the upper continental mantle is derived in this study. The density of the upper(most) mantle underlying the continental crust is obtained from the estimated values of the crust–mantle (Moho) density contrast. Since the continental crustal thickness varies significantly, these upper mantle density values to a large extent reflect the density changes with depth. The estimation of the Moho density contrast is done through solving Moritz’s generalization of the Vening-Meinesz inverse problem of isostasy. The solution combines gravity and seismic data in the least-squares estimation model. The estimated upper mantle density (beneath the continental crust) varies between 2770 and 3649 kg/m3. The upper mantle density increases almost proportionally with depth at a rate of 13±2 kg/m3 per 1 km at the investigated depth interval from 6 to 58 km.